Financial accounting - Matulich, Serge; Heitger, Lester E. (New York : McGraw-Hill, 1980)
This book is the financial accounting volume of a coordinated two-volume finance / managerial set designed for introductory accounting courses.
Includes bibliographical references and index.
hza 07/09/2018
Loans
Keywords: Accounting; Financial Accounting